Determining the effect of edible gelatin, agar-agar, and chitosan coatings on the storage of cucumber fruits - Pusik, Ludmila; Bondarenko, Veronika; Pusik, Vlаdimir; Serhiienko, Oksana; Terokhina, Liudmyla; Gurin, Maxim; Soldatenko, Oleksii; Voitsekhivskyi, Volodymyr; Muliarchuk, Oksana; Orlovsky, Mykola (Eastern-European Journal of Enterprise Technologies, 2026)
This study examines the technology of pre-treating cucumber fruits using edible coatings based on gelatin, agar-agar of various concentrations, as well as chitosan with the addition of garlic essential oil. The task addressed is to identify safer and more effective post-harvest treatment technologies for cucumbers, which could reduce produce losses during storage and extend their shelf life. The materials under investigation were cucumber fruits, gelatin, agar-agar, chitosan, as well as garlic essential oil. The ratio of gelatin to agar-agar in the coating matrix gelatin:agar-agar was 100%:0; 0:100; 75%:25%; 50%:50%; and 25%:75%, with chitosan at 1%. The influence of this coating on water-holding capacity, physicochemical, structural-mechanical, and microbiological parameters of cucumber fruits was evaluated. It was established that treatment with edible compositions significantly (НІР05 = 0.79) reduces natural weight loss of cucumbers during storage at a temperature of 15±1°C to a range of 3.1% to 3.6%. Weight loss in untreated fruits amounted to 4.7%. The agar-agar-based coating provided the lowest weight loss of 3.1%. It was shown that daily weight loss of cucumbers ranged from 0.63% to 0.75% when treated with edible compositions. Untreated fruits lost up to 1.37% of their weight daily. The addition of 2% garlic essential oil to the coating inhibited the development of microorganisms by 1.5–1.7 times. The study found that after 6 days of storage, the coated fruits exhibited 11.2% higher elasticity than the control group, and 18.5% higher at the end of the storage period. The effectiveness of the edible coating was confirmed by correlation coefficient r = 0.9317–0.9881